Research of the assortment and information support of medical products and cosmetics - I. Ya. Horodetska; О. R. Levytska; I. L. Chukhraу (The State Expert Center of the Ministry of Health of Ukraine, 2022)
An urgent problem of the contemporary domestic pharmaceutical market is the availability of a large number of products and goods that are not registered as medicines in the prescribed manner, but declare in different ways the medicinal properties and uses for therapeutic purposes. Without unified and comprehensible information resources on such products, this function is partially performed by the site Compendium.onLine. The aim of the research was to consider of the assortment and accompanying information of medical products and cosmetics. The object of our study was the data provided by the Internet resource Compendium.onLine. The subgroup «Liquids» from group 13 «Other products for treatment» of the section «Medical devices» and group 06 «Cosmetics for health» from the section «Cosmetics» were selected for the analysis, as their assortment was more typical for pharmacies. 147 items were presented in the subgroup «Liquids», which were offered by 51 manufacturers, one third of which were native companies. The predominant form of release was nasal spray - 42.2%, solutions (including for inhalation, for the oral cavity, ophthalmology, ear hygiene, for nails) represented 12.9% of the range items, eye drops - 8.2%, and throat spray - 4.8%. The subgroup «Cosmetics for Health» contained 634 products, which were produced by 163 manufacturers, two thirds of which were native firms. The predominant forms of release were cream (20.3%), gel (13.2%) and balm (11.5%). It was found that the analysed subgroups included some tools, the release forms of which did not correspond to the names of these subgroups. 94.3% of the range of health cosmetics contains recommendations for medical use. At the same time, 26.0% of them were diagnosed according to the International Classification of Diseases. Health cosmetics offered by drug manufacturers in 100% of cases have recommendations for their medical use. As cosmetics are not medicines, it is prohibited by law to declare their medicinal properties. The study made it possible to characterize the structure of the range and accompanying information of two subgroups of medical products and cosmetics, the nomenclature of which is more typical of pharmacies. The problems inherent in the circulation of these groups of pharmaceutical products were identified and ways to solve them were suggested.